2016
DOI: 10.1073/pnas.1604090113
|View full text |Cite|
|
Sign up to set email alerts
|

Emergence of ion channel modal gating from independent subunit kinetics

Abstract: Many ion channels exhibit a slow stochastic switching between distinct modes of gating activity. This feature of channel behavior has pronounced implications for the dynamics of ionic currents and the signaling pathways that they regulate. A canonical example is the inositol 1,4,5-trisphosphate receptor (IP3R) channel, whose regulation of intracellular Ca2+ concentration is essential for numerous cellular processes. However, the underlying biophysical mechanisms that give rise to modal gating in this and most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 63 publications
0
10
0
Order By: Relevance
“…This suggests that K V 7.2/K V 7.3 channels in their second mode of activity are more sensitive to PI(4,5)P 2 depletion. Modal gating has been documented in the activity of many types of channels and it has been shown to be critically involved in their function (Nilius, 1988;Marrion, 1993;Naranjo and Brehm, 1993;Zahradnikova and Zahradnik, 1995;Zahradnikova et al, 1999;Magleby, 2004;Tanskanen et al, 2005;Chakrapani et al, 2011;Bicknell and Goodhill, 2016). To understand modal gating, it is essential to define what a "mode" is.…”
Section: Modal Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that K V 7.2/K V 7.3 channels in their second mode of activity are more sensitive to PI(4,5)P 2 depletion. Modal gating has been documented in the activity of many types of channels and it has been shown to be critically involved in their function (Nilius, 1988;Marrion, 1993;Naranjo and Brehm, 1993;Zahradnikova and Zahradnik, 1995;Zahradnikova et al, 1999;Magleby, 2004;Tanskanen et al, 2005;Chakrapani et al, 2011;Bicknell and Goodhill, 2016). To understand modal gating, it is essential to define what a "mode" is.…”
Section: Modal Behaviormentioning
confidence: 99%
“…For RyR2, KcsA, and some neuronal receptors such acetylcholine and NMDA receptors that undergo desensitization (Nilius, 1988;Magleby, 2004;Bicknell and Goodhill, 2016), modal gating is correlated with the decrease of channel activity as activation is prolonged. However, this is not the case in K V 7 channels.…”
Section: Modal Behaviormentioning
confidence: 99%
“…Further, for heterogeneous portions in the record to reflect a true mode shift, the recorded signal must originate from the same channel thus requiring recordings from one-channel patches. Despite these impediments, evidence is accumulating that modal gating is a universal property of ion channels that shapes their functional output and is biologically regulated 9092 .…”
Section: Modeling the Operation Of Nmda Receptorsmentioning
confidence: 99%
“…Indeed, electrophysiological measurements showed that point-mutations at E71 lock the KcsA channel into different, natively occurring gating modes, which are best represented by a high-open probability (E71A), a low-open probability (E71I), and a high-frequency flicker (E71Q) mode 6 . Random shifts between such gating modes, known as modal gating shifts, were observed in various eukaryotic and prokaryotic K + channels, and are a widespread regulatory mechanism of channel activity 4,711 . Yet, despite their broad functional importance, the structural correlates and triggers of modal gating shifts are unknown.…”
Section: Introductionmentioning
confidence: 99%